2013
DOI: 10.1039/c2an36185j
|View full text |Cite
|
Sign up to set email alerts
|

Quantification by SIFT-MS of acetaldehyde released by lung cells in a 3D model

Abstract: Our previous studies have shown that both lung cancer cells and non-malignant lung cells release acetaldehyde in vitro. However, data from other laboratories have produced conflicting results. Furthermore, all these studies have been carried out in 2D models which are less physiological cell growth systems when compared to 3D models. Therefore, we have carried out further work on the release of acetaldehyde by lung cells in 3D collagen hydrogels. Lung cancer cells CALU-1 and non-malignant lung cells NL20 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 19 publications
(41 reference statements)
0
37
0
Order By: Relevance
“…While analyzing cells in the standard tissue culture setting (which usually provides optimized growth conditions) may provide a first approximation, the task for the future is to imitate the real conditions present in the body. The effect of changing growth conditions on VOC production has been noted in the analysis of tumor cells growing in 2D versus 3D cultures, the latter being more similar to in vivo conditions of the tumor growth [118]. Availability of nutrients and oxygen in tissue is typically optimized in the in vitro experiments and may thus differ considerably from the situation in the tissue.…”
Section: Biochemical Processes Underlying Voc Productionmentioning
confidence: 99%
“…While analyzing cells in the standard tissue culture setting (which usually provides optimized growth conditions) may provide a first approximation, the task for the future is to imitate the real conditions present in the body. The effect of changing growth conditions on VOC production has been noted in the analysis of tumor cells growing in 2D versus 3D cultures, the latter being more similar to in vivo conditions of the tumor growth [118]. Availability of nutrients and oxygen in tissue is typically optimized in the in vitro experiments and may thus differ considerably from the situation in the tissue.…”
Section: Biochemical Processes Underlying Voc Productionmentioning
confidence: 99%
“…Nevertheless, do the cell lines growing in vitro have similar characteristics to in vivo cancer cells? A 3D model has been proposed [120] in which the cells were cultured in 3D scaffolds composed of collagen type I hydrogels, compared to 2D models where cells are grown on surfaces such as plastic or glass. Quantification by SIFT-MS of cells lines headspace CALU-1 and non-malignant lung cells NL20 revealed that the amount of acetaldehyde released by both cell types grown in a 3D model is higher when compared to that of the same cells grown in 2D models.…”
Section: Disease Diagnosismentioning
confidence: 99%
“…Results of studying different lung cancer cell lines in 2D cultures suggested that altered VOC production can be detected in the early stages of carcinogenesis, and can represent a basis for noninvasive diagnosis of lung cancer. Therefore, 2D studies on various normal or cancer cell lines showed either an increase or decrease in several volatile compounds classes such as alkanes, aldehydes, aromatic compounds or alcohols [25, [165][166][167][168][169][170][171][172]. A recent study uses both cancerous and noncancerous lung cell lines grown in 3D scaffolds of collagen type I hydrogel [167].…”
Section: In Vitromentioning
confidence: 98%
“…Therefore, 2D studies on various normal or cancer cell lines showed either an increase or decrease in several volatile compounds classes such as alkanes, aldehydes, aromatic compounds or alcohols [25, [165][166][167][168][169][170][171][172]. A recent study uses both cancerous and noncancerous lung cell lines grown in 3D scaffolds of collagen type I hydrogel [167]. Although the study provides limited data by employing only two cell types, the 3D culture method offers clear advantages over classical 2D approaches by better resembling the physiological situation of cells growing in vivo.…”
Section: In Vitromentioning
confidence: 99%